Analysis of the internship program at UTFPR campus Toledo and its impact on the business environment - Ostroski, Diane Aparecida; Pessoa, Patrícia das Neves; Previatti, Andressa; Kozima, Laís (Seven Editora, 2023)
In the current scenario, most academics in the civil engineering course have difficulty finding companies where they can intern. To assist in this process, the present study sought to identify the profile of the intern demanded by companies in the field of civil construction in the municipality of Toledo, west of Paraná. For that, questionnaires with semi-structured questions were applied to local entrepreneurs. In addition, we sought to analyze the participation and effectiveness of the UTFPR internship program to improve the relationship between the University and the Company and, consequently, make it more effective. It was noted that the greatest difficulty in finding an internship is not due to a lack of vacancies, but due to the lack of communication between academics, the company, and the internship program. Also, it could be seen that there is no constant search by the institution for companies that offer internships in the city and region, that is, the public/private partnership is in deficit DOI: https://doi.org/10.56238/devopinterscie-003